Scanning electron microscopy assessment of tubular penetration depth of root canal sealers combined with different obturation techniques - Cvjetićanin, Milica; Ramić, Bojana; Vukoje, Karolina; Drobac, Milan; Stojanac, Igor; Petrović, Ljubomir (Vojnosanitetski pregled, 2023)
Background/Aim. The ability to effectively and consistently penetrate dentinal tubules is considered a favorable factor for the evaluation of root canal sealers (RCSs). The aim of the study was to assess the penetration depth into dentinal tubules of three RCSs combined with four obturation techniques. Methods. The mesial canals of 66 extracted human mandibular molars were endodontically prepared and randomly allocated into 12 experimental groups depending on the RCS type used (AH Plus™, EndoREZ™, Sealapex™) as well as the obturation technique applied [cold lateral compaction, cone-fit, carrier-based (with heated gutta-percha), warm vertical compaction]. Using scanning electron microscopy, transversal root cross-sections were analyzed, and the maximum depth of RCS penetration was measured (396 sections, in total, corresponded to the apical, middle, and coronary third). Results. Group AH Plus™/warm vertical compaction yielded the highest penetration depth – 1,165 μm, followed by EndoREZ™/cone-fit – 1,154 μm; the lowest depth was measured for EndoREZ™/warm vertical compaction – 502 μm. The mean value of the maximum penetration depth of RCS yielded 1,204 μm in the coronary thirds, 1,005 μm in the middle thirds, and 770 μm in the apical thirds. The AH Plus™ RCS penetrated deeper into dentinal tubules when the obturation techniques with heated gutta-percha were applied, while the opposite findings were obtained for the EndoREZ™ RCS. Conclusion. According to our research, the RCS penetration depth appears to be influenced by the RCS type used, as well as the obturation technique applied.